Peringatan Darurat Indonesia Kasus Putusan Rancangan Undang-Undang Pilkada: Studi Ilmu Sosial dan Ilmu Politik - M Leliko Ariyan Jaya (Journal of Sharia and Legal Science, 2025)
The viral emergency alert on social media stemmed from a controversial Constitutional Court decision regarding Indonesia’s local elections. The Court ruled to lower the electoral threshold for political parties and allowed candidates to meet the age requirement (30 years) at the time of registration rather than at inauguration. However, the legislature quickly responded with a conflicting decision the following day. This study aims to examine how power should operate within the framework of democratic governance and the trias politica principle. Using a descriptive qualitative approach, the research explores the imbalance and potential manipulation of power among the legislative, executive, and judicial branches. The rapid reversal of crucial decisions indicates a concentration of power that bypasses institutional checks and balances. Public dissatisfaction was evident in protests and widespread discourse, signaling a crisis of trust in state institutions. The disruption of democratic mechanisms may lead to long-term consequences, including corruption, social inequality, and authoritarianism. In a democratic state, where sovereignty lies with the people, such political instability endangers the legitimacy and effectiveness of governance.